Examining the influence of problematic internet use on sleep quality in Chinese adolescents: a study using the extended Stressor-Strain-Outcome (SSO) model - Gong, Zhuliu; Guo, Yi; Fan, Siyuan; Sun, Xinying; Wu, Yibo (Frontiers in Psychology, 2024)
Objective: This study aims to explore how problematic internet use may affect the sleep quality of Chinese adolescents using the extended Stressor-Strain-Outcome (SSO) model. The model posits that stressors indirectly influence behavioral outcomes through the mediation of emotional and physiological strain responses.Objective: This study aims to explore how problematic internet use may affect the sleep quality of Chinese adolescents using the extended SSO model. Method: A sample of 4,365 adolescents in China participated in this study, which utilized questionnaires and other methods to develop a novel SSO model. In this model, problematic internet use was considered as the stressor, anxiety as an indicator of tension, and sleep quality as the ultimate outcome. Family health was introduced as a moderating variable. The model's validity was confirmed using professional statistical software, including SPSS 26.0 and SmartPLS 4.0. Results: The study found that problematic internet use can significantly and positively predict adolescents' anxiety (β = 0.132, Pp < 0.001) and sleep quality (β= 0.362, P p < 0.001). Furthermore, anxiety was identified as a significant mediating factor between problematic internet use and sleep qualitquality ［ Effect=0.066 ， Pp ＜ 0.05 ， 95%CI(0.014，-0.0018)］ (0.14, 0.18). Family health was observed to have a moderating effect on the relationship between problematic internet use and anxiety (β = -0.075, p < 0.001).The research indicates that problematic internet use not only directly increases individual anxiety as a stressor but also indirectly impacts sleep quality by exacerbating anxiety. However, a positive family health status can effectively moderate the adverse impact of problematic internet use on anxiety.